Maximizing Profitability: The Lean Way To Sustainable Manufacturing - Rachmawati, Christina; Mahmudy, Wayan Firdaus; Moh. Khusaini; Kurniawan, Andi (Accounting Department,, 2025)
Purpose - This quantitative study examines the impact of lean production practices on the financial performance and sustainability of Indonesian FMCG companies. By analyzing waste reduction, efficiency improvements, and eco-design integration, the research demonstrates that lean practices significantly enhance both financial performance and environmental responsibility. These findings offer valuable insights for multinational companies operating in similar contexts. Design/methodology/approach - This research employs a quantitative approach to discern the contribution of lean way to sustainable manufacturing. Through a comprehensive survey and meticulous observation, this work maps the intricate ways in which lean production practices affect economic and business outcomes, providing valuable insights into the real-world application of lean principles. Findings -. This case study demonstrates how lean production methods can substantially benefit a company's financial performance and overall operations. The implementation of lean production methodologies has a proven track record of improving efficiency, reducing waste, and elevating product and process quality, leading to substantial economic gains and enhanced business performance. Practical implications - Implementing lean production requires careful consideration of technological innovation and organizational culture. Neglecting either aspect poses a significant risk of hindering the successful implementation and realization of the myriad benefits that lean production offers. Originality/value - This article examines an Indonesian FMCG company's experience with lean production, providing a rare glimpse into how these methods are applied in a developing economy. This study aims to expand our understanding of lean production and offer useful guidance to multinational companies operating in comparable settings. Paper type -Case study